2017
DOI: 10.1080/09658211.2017.1364393
|View full text |Cite
|
Sign up to set email alerts
|

Changing beliefs about past public events with believable and unbelievable doctored photographs

Abstract: Doctored photographs can shape what people believe and remember about prominent public events, perhaps due to their apparent credibility. In three studies, subjects completed surveys about the 2012 London Olympic torch relay (Experiment 1) or the 2011 Royal Wedding of Prince William and Kate Middleton (Experiments 2-3). Some were shown a genuine photo of the event; others saw a doctored photo that depicted protesters and unrest. A third group of subjects saw a doctored photo whose inauthenticity had been made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…The rise of photo manipulation paired with people’s apparent insensitivity to such manipulation has consequences across myriad domains, from law enforcement (when photos are used as evidence in court) through to politics (when photos are used to promote a political agenda). Moreover, research shows that doctored photos (and videos) can influence people’s beliefs, memories, intentions and behaviors (e.g., Nash, 2017; Sacchi, Agnoli, & Loftus, 2007; Wade, Garry, Read, & Lindsay, 2002; Wade, Green, & Nash, 2010). The current research does not provide a solution to the complex problem of how to detect image forgeries, but the results suggest that people might frequently neglect potentially useful cues in images.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of photo manipulation paired with people’s apparent insensitivity to such manipulation has consequences across myriad domains, from law enforcement (when photos are used as evidence in court) through to politics (when photos are used to promote a political agenda). Moreover, research shows that doctored photos (and videos) can influence people’s beliefs, memories, intentions and behaviors (e.g., Nash, 2017; Sacchi, Agnoli, & Loftus, 2007; Wade, Garry, Read, & Lindsay, 2002; Wade, Green, & Nash, 2010). The current research does not provide a solution to the complex problem of how to detect image forgeries, but the results suggest that people might frequently neglect potentially useful cues in images.…”
Section: Discussionmentioning
confidence: 99%
“…One such area of study is the effect of 'fake news', and many studies have attempted to plant false memories for fabricated political events (e.g. Frenda et al, 2013;Murphy et al 2019;Nash, 2018;Saachi et al, 2007). A 2018 meta-analysis showed that misinformation related to real-world events is more challenging to correct than constructed misinformation (e.g., referring to a fictional crime), and that misinformation pertaining to politics is especially resistant to retraction (Walter & Murphy, 2018).…”
mentioning
confidence: 99%
“…In recent years, interest has grown in how information processing across depth impacts attention and memory of scene representations (Bonner & Epstein, , 2018Josephs & Konkle, 2019;Man et al, 2019). Traditionally, studies of depth perception have examined observers' estimates of distance (Cutting & Vishton, 1995;Nagata, 1991) and how information at different distances is processed: from peripersonal to vista space (Costantini et al, 2011;Cutting & Vishton, 1995;Previc, 1998).…”
Section: Spatial Processing Across Depth and Attentional Processesmentioning
confidence: 99%
“…Recent studies on scene processing have also shown qualitatively different processing of spaces closer to the observer (Bonner & Epstein, 2017, 2018Fernandes & Castelhano, 2021;Josephs & Konkle, 2019;Man et al, 2019). Most recently, Castelhano and Fernandes (2021) found a foreground bias when examining rapid scene perception for images that had mismatched scene categories in the foreground and background (i.e., chimera scenes).…”
Section: Spatial Processing Across Depth and Attentional Processesmentioning
confidence: 99%